Signal Strength of VLF Radio Wave Measured at Syowa Station in Antarctica - Toshirou SAKAMOTO; Isao SHIRO (National Institute of Polar Research, 1976)
The measurement of NAA-17.8 kHz signal strength was made at Syowa Station, Antarctica, for one year from February 1970 to January 1971. The diurnal and seasonal variations of the signal strength are shown. The data were compared with other observational data associated with auroral phenomena and solar flares. A significant positive correlation between VLF signal strength and radio aurora occurrences was found during the nighttime. Sudden enhancements of the signal were detected, which appear to be related to the solar flares.